Using Siblings to Estimate the Effect of School Quality on Wages - Altonji, Joseph G.; Dunn, Thomas A. (The Review of Economics and Statistics, 1996)
In this paper we use the variance across siblings in school characteristics to estimate the effects of school inputs on wages. The analysis uses sibling pairs from the National Longitudinal Surveys of Labor Market Experience of Young Men and Young Women. We find that teacher's salary, expenditures per pupil, and a composite index of school quality indicators have a substantial positive effect on the wages of high school graduates.